Disparity of Gut Microbiota Composition Among Elite Athletes and Young Adults With Different Physical Activity Independent of Dietary Status: A Matching Study - Xu, Yongjin; Zhong, Fei; Zheng, Xiaoqian; Lai, Hsin-Yi; Wu, Chunchun; Huang, Cong (Frontiers in Nutrition, 2022)
Objective: This study aims to investigate whether the discrepancy of gut microbiota among elite athletes and young adults with different physical activity independent of dietary status. Methods: An age and sex matching study were conducted between April and May 2021 in Hangzhou, China. A total of 63 Chinese young adults were recruited in this study and divided into elite athlete group, physically active group, and physically inactive group according to the principle of equal proportion. The fecal samples were collected to assess gut microbiota composition. Dietary status was measured with food-frequency questionnaire. Comparisons in gut microbiota among three groups were analyzed analysis of covariance. Results: A tendency to form clusters was showed for beta diversity among three groups, while no significant difference was observed in alpha diversity. In multiple analysis model by adjusting dietary status, although no significant characteristics were observed for the composition of gut microbiota in elite athletes compared to young adults with low physical activity, beneficial bacteria linked to health such as Actinobacteria class (p=0.005) and Ruminococcus genus (p=0.033), bacteria associated with anti-inflammatory such as Lactobacillales order (p=0.057), Lachnospiraceae (p=0.097), Fusicatenibacter genus (p=0.153) were abundant in young adults with high physical activity compared to young adults with low physical activity. These discrepancies in gut microbiota among athletes and young adults were independently of dietary status. Conclusion: This matching study showed that physically active young adults are more likely have higher abundance of beneficial bacteria and anti-inflammatory bacteria of gut than elite athletes and physically inactive young adults after adjusting dietary status. These findings revealed a non-linear association between physical activity and gut microbiota.